LABORATORY QUALITY MANAGEMENT - Katerina Tosheska-Trajkovska (Institute of Knowledge Management, 2020)
Abstract: Laboratories in the Republic of North Macedonia are subject to many national requirements. Each laboratory should deliver quality laboratory service for patients in accordance to national regulations and requirements. The International Organization for Standardization (ISO), has developed quality systems to assess specific aspects of health services. A majority of laboratories rely on International Quality Standards known as ISO/IEC/17025 for all types of testing and calibrating laboratories and more specifically ISO 15189 for medical laboratories. These standards are quite comprehensive and often very resource-intensive. Medical laboratories were early leaders in efforts to minimize medical errors and improve patient safety. A quality management system (QMS) is a vehicle to deliver a quality service. The importance of quality in the functioning of health care laboratories is well recognized globally. The poor quality of laboratory results can lead to inappropriate interventions, adversely affect the credibility of the laboratory and may also invite legal action. It is, hence, essential to develop and implement a policy on quality in health laboratories. The QMS defines the organizational structure, responsibilities, policies, procedures, standards and resources required. What is needed is a roadmap for quality that ensures that each laboratory makes its best contribution to patient care and safety.The laboratory quality system essentials are:Organization;Facilities;Personnel; Equipment; Purchasing and inventory. The work quality system essentials are: Process control;Documents and records and Information management. The measurement quality system essentials are:Occurrence management; Assessments: external and internal; Customer service and Process improvement. An important relationship between quality activities that should be designed and supported by laboratory management and the technical activities that produce laboratory results for patient care should exist.Different laboratories are at different levels of quality development and hence a flexible step-wise approach has to been followed.Laboratories not implementing a good quality management system are guaranteed that there will be many errors and problems occurring that may go undetected. Implementing a quality management system may not guarantee an error-free laboratory, but it does yield a high-quality laboratory that detects errors and prevents them from recurring. Identification of a national focal point for laboratories, along with a well-defined national laboratory policy is essential. It is suggested that subsequent to the development of minimum national standards, countries should strive to make these mandatory. Implementation of international standards can be undertaken subsequently through up gradation of national standards.
Keywords: quality management; medical laboratories; ISO standard 15189